2014
DOI: 10.7314/apjcp.2014.15.15.6081
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Microlux/DLTM Chemiluminescence Device in Screening of Potentially Malignant and Malignant Oral Lesions

Abstract: Background: To evaluate the effectiveness of Microlux/DL with and without toluidine blue in screening of potentially malignant and malignant oral lesions. Materials and Methods: In this diagnostic clinical trial clinical examination was carried out by two teams: 1) two oral medicine consultants, and 2) two general dentists. Participants were randomly and blindly allocated for each examining team. A total of 599 tobacco users were assessed through conventional oral examination (COE); the examination was then re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…28 Ibrahim et al found that the sensitivity was 100% and the specificity was 32.4% in the visualization of suspicious premalignant lesions using Microlux/DL. 29 In our study, the sensitivity of leukoplakia detection was 57%, which was lower than in the abovementioned results, but the specificity of 74% was significantly higher than the ViziLite ® application by Sambandham et al Honsi et al used image cytometry to determine DNA ploidy in LP. The most common degree of DNA ploidy in LP lesions was diploidy.…”
Section: Actual Diagnosiscontrasting
confidence: 73%
“…28 Ibrahim et al found that the sensitivity was 100% and the specificity was 32.4% in the visualization of suspicious premalignant lesions using Microlux/DL. 29 In our study, the sensitivity of leukoplakia detection was 57%, which was lower than in the abovementioned results, but the specificity of 74% was significantly higher than the ViziLite ® application by Sambandham et al Honsi et al used image cytometry to determine DNA ploidy in LP. The most common degree of DNA ploidy in LP lesions was diploidy.…”
Section: Actual Diagnosiscontrasting
confidence: 73%
“…Altered epithelial cells cause the appearance of “aceto-white” lesions, and LED light source makes the lesion more easily recognisable. Furthermore, the use of TB can be used in conjunction with Microlux/DL TM , to enhance the visualisation of dysplastic areas ( Ibrahim et al, 2014 ). In 2009 was conducted a study on 50 patients with oral white lesions to evaluate the efficacy of Microlux/DL TM .…”
Section: Other Devicesmentioning
confidence: 99%
“…8-94.3 70.7-99.6 (McIntosh et al 2009;Ibrahim et al 2014) Orascoptic DK n/a n/a (Patton et al 2008) VELscope 30-100 15-100 (Poh et al 2006;Balevi 2007;Patton et al 2008;Trullenque-Eriksson et al 2009;Mehrotra et al 2010;Moro et al 2010;Awan et al 2011a;Balevi 2011;Fricain 2011;Lopez-Jornet and De la Mano-Espinosa 2011;Scheer et al 2011;Farah et al 2012;Marzouki et al 2012;Bhatia et al 2013) Photodynamic diagnosis 79-100 50-99 (Leunig et al 2000;Betz et al 2002;Zheng et al 2002;Chang and Wilder-Smith 2005;Sharwani et al 2006a;Driemel et al 2007;Sieron et al 2008) Optical diagnostic technologies…”
Section: Chemiluminescencementioning
confidence: 99%
“…The oral cavity is examined with a battery-powered LED fiber-optic source that emits a blue-white light (Patton et al 2008;Ibrahim et al 2014). Few studies have been published on its effectiveness in oral PMD diagnosis (McIntosh et al 2009).…”
Section: Chemiluminescencementioning
confidence: 99%
See 1 more Smart Citation